Investigating the impact of code switching on student’s engagement in the teaching and learning of French as a Foreign Language in Secondary schools in Education - Moeketsi Petrose RAPULENG (Department of French Language Education, Universitas Pendidikan Indonesia, 2024)
Multilingual pedagogical strategies are instructional methods that take into account the multilingual nature of the classroom. These strategies are designed to accommodate students who speak different languages and help them to learn effectively in multilingual environment. The present study investigates the impact of code switching on students’ engagement in the teaching and learning of French as a Foreign Language (FFL) in secondary schools. The theory of Constructivism underpinned this study. The study adopted mixed method, explanatory sequential research design study where data was generated through the pre-test and post-test, focus group interviews and structured observations. The data was analysed using the SSPS. The study reveals that code switching helps learners to understand better French content, it also helps learners to be interactive in class which may ameliorate the performance of learners. Teachers are advised to use code-switching in the teaching and learning of French as a Foreign Language (FFL). The is a need to conduct a study on how teachers can best use code-switching in the teaching and learning of FFL.Keywords: Code switching, Student Engagement, French as a Foreign Language